PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, EXCHANGE RATE, CAPITAL INTENSITY DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK - Djati, Kartika (Jurnal Riset Akuntansi Politala, 2023)
The purpose of this study is to empirically determine the influence of independent commissioners, audit committees, exchange rates, capital intensity and profitability on tax avoidance. The population of this study includes all manufacturing companies in the consumer goods industry listed on the Indonesia Stock   Exchange   (IDX)   for   the   period   2016-2020. Sampling   techniques use purposive sampling using regression analysis of panel data in knowing the relationship between independent and dependent variables. This type of research method is quantitative with an associative level of explanatory. Based on the criteria that have been determined obtained by 10 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is regression analysis of panel data with the help of Eviews 13.0 software. The results showed that the Independent Commissioner, Exchange Rate and Profitability had no effect on Tax Avoidance whereas the Audit and Capital Intensity Committee had a significant effect on Tax Avoidance.